2015
DOI: 10.1007/s11356-015-4756-4
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of DDTs in maricultured fish: a modeling study in South China

Abstract: Fish is one of the most important nutrition sources for humanity. Contaminant exposure risk in fish farming will eventually deliver to the crowd through diet. China is the largest fish producing as well as exporting country, where mariculture plays an important role in fish production, especially in South China. Previous investigations indicated that a variety of compartments in farming areas of South China Sea were polluted by persistent organic pollutants, including DDT (dichlorodiphenyltrichloroethane) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The limitation conditions of the trophic structure of Daya Bay waters gradually changed from N limited at the end of the last century to P limited, and this trend could become more prominent in the future. [48] and pollution. The discharge of liquid waste during aquaculture leads to higher than normal levels of pollutants in adjacent waters, which has a significant impact on the ecological functions of water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation conditions of the trophic structure of Daya Bay waters gradually changed from N limited at the end of the last century to P limited, and this trend could become more prominent in the future. [48] and pollution. The discharge of liquid waste during aquaculture leads to higher than normal levels of pollutants in adjacent waters, which has a significant impact on the ecological functions of water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, our previous modeling study in Hailing Bay and Daya Bay found that DDTs tended to transport from sediment to water in the mariculture zone (Fang et al, 2016). Contaminated sediment contributed 6.5% (0e26%) and 7.3% (0e28%) to the loadings of DDTs in snubnose pompano (Trachinotus blochii) and saddletail snapper (Lutjanus malabaricus), respectively (Fang et al, 2016).…”
mentioning
confidence: 87%
“…Our previous studies have accumulated abundant data in two estuarine bays, i.e., Daya Bay and Hailing Bay (Fig. 1), of South China (Fang et al, 2016;Guo et al, 2009;Liu et al, 2013;Yu et al, 2011a,b), which presented the possibility to evaluate the impacts of DDT released from antifouling paints with a comprehensive modeling study. Because of its dominance among all DDT components (including o,p 0 -and p,p 0 -DDT, DDE, and DDD) in antifouling paints, p,p 0 -DDT was selected as the target compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of synthetic compounds has included polycyclic aromatic hydrocarbons that have been linked to the operation of boats supporting aquaculture infrastructure (Klumpp et al 2002;Yu et al 2012). Various persistent halogenated compounds (PHCs), pesticides such as DDT (dichlorodiphenyltrichloroethane), and pharmaceuticals have originated in feed (Yu et al 2011b;Chen et al 2015;Fang, Bao and Zeng 2016). The release of pharmaceuticals from aquaculture in China has been reviewed previously and, in the context of coastal aquaculture, has included high levels of sulfonamides that can cause the occurrence of antibiotic-resistant genes (He et al 2016).…”
Section: Chemical Impactsmentioning
confidence: 99%